Application of Medication Compliance Therapy and Scheduled Activities: Prayer in Hearing Hallucinations - Widiawati, Mela; Asep Riyana; Kustiawan, Ridwan (Asy-Syifa : Journal of Science and Technology Nursing, 2024)
Objective: The purpose of this study was to provide an overview of health education including medication adherence, planned activities, and spiritual prayer as a means to help people with auditory hallucinations. Methods: The research method used is a qualitative method, which is a method used to collect data through observation of people, interviews, or observation of behaviour, conducted in April-March 2024. Results: Based on the nursing care case study conducted, from the data analysis obtained data from client 1 and the factors causing hallucinations, the client has experienced losing her husband, while client 2 is the perpetrator who experiences hallucinations because the client has lost the house, namely blown away. Interventions carried out on client 1 and client 2 are Sp 1 to Sp 4 Auditory Hallucinations with additional therapy Application of taking medication and Scheduled activities: Prayer. Implementation is the application of Sp 1 to Sp 4 Hallucinations coupled with the application of compliance therapy taking medication and scheduled activities: Prayers in accordance with the interventions that have been applied. Evaluation is the implementation stage carried out on both clients. Conclusion: Both patients experienced the same problem, namely sensory perception disorders, auditory hallucinations and after being given medication compliance therapy and scheduled activities.